Analisis Dampak Pandemi COVID-19 terhadap UMKM Jasa di Kota Pekanbaru (Studi Kasus UMKM Jasa Penjahit) - Ika Rama Devi; Eka Armas Pailis (JIP ( Jurnal Industri dan Perkotaan ), 2022)
The position of micro, small and medium enterprises (MSMEs) has very important function for a region, especially as one of the pioneers of regional economic growth. The activities of micro, small and medium enterprises (MSMEs) are one way for regional creative products to be recognized and provide business opportunities for business actors in the region. MSMEs 4.0 are starting to recognize advances in computerization, artificial intelligence, robotics, and materials science that can accelerate the shift towards more environmentally friendly products of all types. This study aims to see the impact of the Covid 19 Pandemic on the condition of MSMEs during the COVID-19 pandemic in Pekanbaru City. Practically, the results of this study obtained information about the condition of MSMEs and as a reference for comparison. The research was carried out for 1 month from December 2021. The research method used was descriptive quantitative using snowball sampling technique with information sources in the form of questionnaire interviews with the number of samples found 42 MSME Tailor Services. . The results of research on operating profits obtained by tailoring SMEs in Pekanbaru City during the COVID-19 pandemic showed a decrease in turnover. The data illustrates that there are still many tailoring service businesses that do not know the potential of their business so they cannot read market opportunities. The PSBB (Large-Scale Social Restrictions) policy implemented by the government which closed school and office children was the main cause of the decline in the income of service business owners. The step that must be taken by business owners to deal with the impact of the Covid19 pandemic is to develop social and digital strategies to respond to changes that occur in the market by implementing social and digital strategies to respond to changes in the market market by implementing social and digital strategy development.